Particularidades da transferência no atendimento psicológico online em um serviço de telepsicologia universitário - Prux, Isabela Bressan (My University, 2024)
In recent years, technological development has transformed people's lives, especially in communication, with the increased access to the internet. Alongside this, the COVID-19 pandemic has accelerated the adoption of communication technologies, including online clinical psychology, due to the need for social isolation. In response to this, the Federal Council of Psychology has regulated online counseling, emphasizing the importance of the patient-psychologist relationship. Psychoanalysis, being one of the theoretical and clinical approaches used by psychologists, emphasizes the transference relationship, and for this reason, it may face challenges in the online modality, requiring flexibility in technique. In this context, this work aims to describe specific aspects of remote psychoanalytic psychology in relation to transference because it deviates from the classic model of in-person sessions within the office setting and with extended durations. The research consists of a qualitative exploratory study, composed of semi-structured interviews conducted in both in-person and remote formats. Psychologists who worked in the telepsychology service at the University of Caxias do Sul (UCS) between 2020 and 2022 were interviewed. This service provides exclusively remote consultations where students or psychologists affiliated with UCS offer free assistance to individuals referred by the public health network of Caxias do Sul.The data obtained were analyzed using the thematic analysis proposed by Braun and Clarke (2006) and categorized into themes that encompass the main peculiarities of the practice. The analysis emphasizes the transference relationship and free association, challenges and potentialities of remote counseling, conditions for expanding the setting, indications and contraindications of remote counseling, manifestations of resistance in the online format, and the specificities of UCS telepsychology. It is noteworthy to emphasize the importance of regulations, training, and ongoing research to enhance the quality of remote sessions. Telepsychology plays a crucial role in promoting access to mental health and should be explored and developed to increasingly meet the needs of society as a whole. [resumo fornecido pelo autor]
Nos últimos anos, o desenvolvimento tecnológico tem transformado a vida das pessoas, especialmente na comunicação, com o aumento do acesso à internet. Junto a isso, a pandemia de COVID-19 acelerou a adoção de tecnologias de comunicação, incluindo a psicologia clínica online, devido à necessidade do isolamento social. Diante dele, o Conselho Federal de Psicologia regulamentou o atendimento online, destacando a importância da relação paciente-psicólogo. A psicanálise, sendo uma das linhas teóricas e clínicas que atuam uma parcela dos psicólogos, enfatiza a relação transferencial, e por este motivo, pode enfrentar desafios na modalidade online, exigindo flexibilidade na técnica. Neste sentido, este trabalho tem por objetivo descrever particularidades existentes na atuação da psicologia de abordagem psicanalítica de forma remota em relação à transferência, isso porque distancia-se do modelo clássico de atendimento, dentro do consultório e com duração estendida. A pesquisa consiste em um estudo qualitativo de natureza exploratória, composto por entrevistas semiestruturada, realizadas de forma presencial e remota. Foram entrevistados psicólogos que atuaram no serviço de telepsicologia da Universidade de Caxias do Sul (UCS), no período entre 2020 e 2022. Este serviço consiste em atendimentos exclusivamente remotos, em que estudantes ou psicólogos vinculados à UCS, prestam de forma gratuita a pessoas encaminhadas pela rede de saúde pública de Caxias do Sul. Os dados obtidos foram apurados através da análise temática proposta por Braun e Clarke (2006) e divididos em temas que abarcam as principais particularidades da prática, enfatizando a relação transferencial e a associação livre, desafios e potencialidades do atendimento remoto, condições para expansão do setting, indicações e contraindicações do atendimento remoto, as manifestações da resistência no online e as particularidades da telepsicologia da UCS. Destaca-se ainda a importância de regulamentações, treinamentos e pesquisa contínua para aprimorar a qualidade dos atendimentos remotos. A telepsicologia desempenha um papel crucial na promoção do acesso à saúde mental e deve ser explorada e desenvolvida para atender, cada vez mais, às necessidades da sociedade como um todo. [resumo fornecido pelo autor]
Keywords: Psicoterapia; Psicoterapeuta e paciente; Pandemias; Psychotherapy; Psychotherapist and patient; Pandémies